2021
DOI: 10.15294/biosaintifika.v13i1.26148
|View full text |Cite
|
Sign up to set email alerts
|

Biodecolorization of Anthraquinone and Azo Dyes by Newly Isolated Indonesian White-Rot Fungi

Abstract: Water pollution by dyes represents from dyestuff industry becomes an environmental concern. Finding new isolates capable of decolorizing these dyes is important. The study aimed to assess the new isolates of white-rot fungi (WRF) as decolorizing agent of anthraquinone and azo dyes. Decolorization assay were conducted in Agar plates and liquid medium. During the decolorization, laccase activities produced by the fungal strains were analyzed. Identification of the fungal strains were investigated using molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…According to Yesilada et al (2018), this phenomenon is possible due to the different physiological characteristics of each WRF fungal strain. Ramadhan et al (2021) found similar findings, which studied decolorization by using Trametes sanguinea, Trametes polyzona and Neofomitella guangxiensis. The results showed that T. polyzona had the highest performance of 95% RB5 and 77% Acid Orange 7 removal while N. guangxiensis could only remove 20-22% of these dyes within 96 hours.…”
Section: Decolorization Of Synthetic Dyes By Three Selected Isolatessupporting
confidence: 73%
See 3 more Smart Citations
“…According to Yesilada et al (2018), this phenomenon is possible due to the different physiological characteristics of each WRF fungal strain. Ramadhan et al (2021) found similar findings, which studied decolorization by using Trametes sanguinea, Trametes polyzona and Neofomitella guangxiensis. The results showed that T. polyzona had the highest performance of 95% RB5 and 77% Acid Orange 7 removal while N. guangxiensis could only remove 20-22% of these dyes within 96 hours.…”
Section: Decolorization Of Synthetic Dyes By Three Selected Isolatessupporting
confidence: 73%
“…The maximum decolorization percentages showed a competitive performance compared to other studies. In the recent work by Ramadhan et al (2021), three newly isolated WRF (Trametes sanguinea, Neofomitella guangxiensis and Trametes polyzona) could remove 59-89% of AB129 in 96 h which was slightly lower than the maximum removal by BRB81 (91%). The BRB 81 also showed a higher decolorization of RBBR dye (51%) compared to other Ceriporia sp.…”
Section: Decolorization Of Synthetic Dyes By Three Selected Isolatesmentioning
confidence: 86%
See 2 more Smart Citations
“…In another experiment, the synthetic dye decolorization capacity of tested fungal strains was evaluated by a semiquantitative agar-plate test that considered the diameter of mycelia and diameter of decolorized zone on a five-point scale (Eichlerov a & Baldarian 2020) to evaluate the extent of decolorization without involving any calculation to determine %decolorization. In a study by Ramadhan et al 2021, the mycelial diameter and diameter of decolorization zone were measured separately and the extent of decolorization was directly correlated to the mycelial diameter but no calculation was done to prove it quantitatively. In this regard, a research group (Si, Cui, and Dai 2013) in their work had devised a quantitative method to calculate the percentage of dye decolorization on solid medium plate as decolorization rate (%) that involves the ratio of diameter of decolorizing circle (or decolorized zone) to the plate diameter (90 mm).…”
Section: Discussionmentioning
confidence: 99%